Analysis of synthesis, accumulation and physicochemical properties of Tartary buckwheat starches affected by nitrogen fertilizer. (1st December 2021) - Gao, Licheng; Xia, Meijuan; Wan, Chenxi; Jia, Yanheng; Yang, Liming; Wang, Meng; Wang, Pengke; Yang, Qinghua; Yang, Pu; Gao, Xiaoli; Gao, Jinfeng
Abstract: Nitrogen fertilizer is a crucial factor affecting the growth and grain quality of Tartary buckwheat. This study was to investigate the synthesis, accumulation, and physicochemical properties of Tartary buckwheat starches under four nitrogen levels (0, 90, 180, 270 kg N ha −1 ). The results showed that activities of four key enzymes, starch contents all first increased and then decreased with increasing nitrogen levels, and peaked at 180 kg N ha −1 . All the starches showed typical A-type, while higher nitrogen levels significantly increased the relative crystallinity. The viscosities significantly decreased, onset, peak, and conclusion first decreased and then increased, while pasting temperature and gelatinization enthalpy increased with increasing nitrogen levels. Nitrogen fertilizer and year had significant effects on the synthesis, accumulation and physicochemical properties of Tartary buckwheat starch, and the nitrogen level of 180 kg N ha −1 was more suitable for planting in the northern area of the Loess Plateau. Highlights: Activities of key enzymes for starch synthesis first increased and then decreased. Amylose content positively correlated with granule bound starch synthase activity. Tartary buckwheat starches under different nitrogen levels all showed A-type. Gelatinization enthalpies significantly increased with increasing nitrogen levels. Nitrogen level of 180 kg N ha −1 was recommended for Tartary buckwheat planting.